Peranan juruukur tanah dalam industri pembinaan - Mohd. Kamarol Bahari, Mohd. Aiman (2014)
Land surveyors works are divided in many areas, for example, in the production of maps, coordinates and position determination, hydrography, cadastral and construction. Some of the Land Surveyors faced problems like not being paid for jobs carried out and some were given jobs which are not clearly defined. The aim of this study is to evaluate the role and problems faced by the land surveyor in the construction industry. The objectives of this study are to identify the scope of work of land surveyors in the construction industry, to identify the problems faced by land surveyors in the construction industry, to find out about payment made to the land surveyors working in the construction industry and to find out the views and opinion regarding freelance land surveyor. This study focuses on land surveyors who are involved in the construction field. The study is carried out by interviews and questionnaires. A total of 30 sets of questionnaires have been collected from the land surveyor and 5 Land Surveyors were interviewed.The data is analyzed using Average Index. From the study, the scope of work for the land surveyor in construction industry are demarcation, setting out the pilling point, marking the grid line according to the plan from engineer/architect ,produce plan, detail survey, and leveling. The problems faced by the land surveyor in construction industry are late payment, issue in cooperation with other parties that does not understand the work of land surveyor and competition from freelance land surveyors.Regarding the payments to the land surveyors, the land surveyors ‘moderate agree’ with the rate of payment. The payments are usually late and only half are received although they had finished their work. From the study, the presence of freelance still does not pose a threat to the Licensed Land Surveyor.